2017
DOI: 10.1016/j.scitotenv.2017.02.056
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of halogenated and organophosphate flame retardants in sediment and fish samples from three European river basins

Abstract: Classic (polybromodiphenyl ethers, PBDEs) and emerging halogenated flame retardants (HFRs) such as decabromodiphenyl ethane (DBDPE) and halogenated norbornenes, as well as organophosphate flame retardants (OPFRs) were analysed in 52 sediments and 27 fish samples from three European river basins, namely the Evrotas (Greece), the Adige (Italy) and the Sava (Slovenia, Croatia, Bosnia and Herzegovina and Serbia). This is the first time that FR levels have been reported in these three European river basins. The hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
46
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(59 citation statements)
references
References 58 publications
10
46
2
1
Order By: Relevance
“…If we take into account that OPFRs represent around 15% by volume of the FR total global production, whereas HFRs represent around 30% by volume, the environmental occurrence of HFRs should be something higher. Moreover, higher bioaccumulation potential of HFRs versus OPFRs has been previously described (Giulivo et al, 2017), as well as limited OPFR biomagnification through food web (Hallanger et al, 2015) probably due to biotransformation processes (Strobel et al, 2018). All these data suggested that HFR levels in dolphins, with a high trophic level, should be higher than those of OPFRs.…”
Section: Opfrs Vs Pbdesmentioning
confidence: 56%
See 1 more Smart Citation
“…If we take into account that OPFRs represent around 15% by volume of the FR total global production, whereas HFRs represent around 30% by volume, the environmental occurrence of HFRs should be something higher. Moreover, higher bioaccumulation potential of HFRs versus OPFRs has been previously described (Giulivo et al, 2017), as well as limited OPFR biomagnification through food web (Hallanger et al, 2015) probably due to biotransformation processes (Strobel et al, 2018). All these data suggested that HFR levels in dolphins, with a high trophic level, should be higher than those of OPFRs.…”
Section: Opfrs Vs Pbdesmentioning
confidence: 56%
“…The occurrence of OPFRs in natural environments was first reported in the late 1970s (Saeger et al, 1979;Sheldon and Hites, 1978). Since then OPFRs have been detected in numerous environmental samples such as in air, wastewater effluent, household dust, sediment, and biota (Brandsma et al, 2015;Giulivo et al, 2017;Kademoglou et al, 2017;Kim et al, 2017;Aznar-Alemany et al, 2018;Herrero et al, 2018). However, their occurrence in the marine environment is not widely reported.…”
Section: Introductionmentioning
confidence: 99%
“…TDCPP is an additive FR and thus is not bound to the matrix and can leach from the products to the environment. TDCPP has been detected in a wide range of environmental media, such as surface water, drinking water, sediment, air, dust, and tissues of wildlife and humans (Brandsma et al, 2013;Cao et al, 2012;Giulivo et al, 2017;Li et al, 2015;Reemtsma et al, 2008). In Sweden, TDCPP was detected in an indoor environment (hospital ward) at a concentration of 150 ng/m 3 (Marklund et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [24] developed an early LC-MS/MS method to determine PFRs in water samples with high performance and quick determination. In recent years, the use of LC-MS/MS has been generalized for screening PFRs in environmental samples as sediment [25][26][27], soil [26], biota [25,[27][28][29], water [16,24], and wastewater [16,30]. The main issues in the analysis of PFRs by LC-MS/MS are interferences and background contamination.…”
Section: Introductionmentioning
confidence: 99%